How to deal with the "new Qaddafi"? Risks and opportunities of Libyan-European rapprochement - Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2004)
Libyan compensation payments to the victims of the La Belle bombing and Chancellor Gerhard Schröder's upcoming visit to Libya represent two more significant steps toward reconciliation between the North African state and the European Union. The rapidity of this normalization process can be explained in terms of shared economic and security interests, but an all too open embrace of this still extremely authoritarian regime harbors the risk of undermining the European initiatives of the Barcelona Process and the European Neighborhood Policy (ENP). The ENP, in particular, makes closer economic cooperation substantially dependent on democratization, good governance, and observance of human rights.(SWP Comments / SWP)
Keywords: 320